A combination of membrane relaxation and shear stress significantly improve the flux of gravity-driven membrane system. (15th May 2020) - Shi, Danting; Liu, Yang; Fu, Wenwen; Li, Jiangyun; Fang, Zheng; Shao, Senlin
Abstract: Gravity-driven membrane (GDM) filtration system is a promising process for decentralized drinking water treatment. During the operation, membrane relaxation and shear stress could be simply achieved by intermittent filtration and water disturbance (created by occasionally shaking membrane model or stirring water in membrane tank), respectively. To better understand the impact of membrane relaxation and shear stress on the biofouling layer and stable flux in GDM system, action of daily 60-min intermission, daily flushing (cross-flow velocity = 10 cm s −1, 1 min), and the combination of the two (flushed right after the 60-min intermission) were compared. The results showed that membrane relaxation and shear stress lonely was ineffective in improving the stable flux, while their combination enhanced the stable flux by 70%. A more open and spatially heterogeneous biofouling layer with a low extracellular polymeric substance (EPS) content and a high microbial activity was formed under the combination of membrane relaxation and shear stress. In-situ optical coherence tomography (OCT) observation revealed that, during intermission, the absence of pushing force by water flow induced a reversible expansion of biofouling layer, and the biofouling layer restored to its initial state soon after resuming filtration. Shear stress caused abrasion and erosion on the biofouling surface, but it exerted little effect on the interior of biofouling layer. Under the combination, however, both the surface and interior of biofouling layer were disturbed because of 1) the water vortexes caused by rough biofouling layer surface, and 2) the porous structure after 60-min intermission. This disturbance, in turn, helped the biofouling layer maintain its roughness and porosity, thereby improving the stable flux of GDM system. Graphical abstract: Image 1 Highlights: Expansion of biofouling layer induced by membrane relaxation was highly reversible. Shear stress decreased the thickness and roughness of the biofouling layer. Expansion of biofouling layer intensified flow disturbance by shear stress. A combination of membrane relaxation and shear stress improved the flux of GDM.